Sistem Informasi Penjualan Elektronik untuk Pengelolaan dan Optimalisasi Transaksi - Maulizar (Jurnal Sistem Komputer (SISKOM), 2021)
The Electronic Sales Information System is designed to streamline the management and optimization of electronic product sales. This system provides a user-friendly interface for managing product listings, tracking sales, and handling customer orders. It allows sales staff to efficiently monitor inventory levels, process transactions, and maintain accurate sales records. By incorporating features such as real-time sales tracking, automated inventory updates, and detailed customer profiles, the system enhances operational efficiency and customer satisfaction. Additionally, the system includes robust reporting and analytics tools that enable management to make informed decisions based on real-time sales data. The system also supports integration with various payment gateways and delivery services, ensuring a seamless and secure transaction process. Overall, the Electronic Sales Information System aims to improve the efficiency and effectiveness of electronic product sales, contributing to increased sales performance and customer satisfaction.